The Effectiveness of Counseling Method based on Thinking, Feeling, and Acting (TFA) on Preoperative Anxiety Levels in Patients with Hand Joint Stiffness - Sena Purwanza; Kurniawan Erman Wicaksono; Reny Tri Febriani; Sih Ageng Lumadi (Universitas Airlangga, 2026)
Introduction: Anxiety is a common phenomenon experienced by patients before undergoing surgical procedures. Pre-operative patients with Hand Joint Stiffness often experience heightened levels of anxiety due to uncertainty about the procedure and its impact on their health condition. To manage pre-operative patient anxiety holistically, the Thinking, Feeling, and Acting (TFA) based counseling method has emerged as a promising approach. Methods: This study aims to evaluate the effectiveness of the TFA-based counseling method on anxiety levels of pre-operative patients experiencing stiffness in the joint hand. The TFA counseling method is holistic, integrating thoughts, feelings, and actions in the counseling process. This study employed a quasi-experimental design with test and control groups. Participants consisted of 30 pre-operative patients with Hand Joint Stiffness s randomly assigned to treatment (received TFA counseling) comprising 15 patients, and control (did not receive counseling) comprising 15 patients. Data collection utilized the Anxiety Questionnaire The-Amsterdam Preoperative Anxiety and Information Scale (APAIS), with a pretest conducted before TFA treatment and a post-test after TFA counseling Results: Data analysis utilized the Statistical Test Paired Sample T-Test to assess the effectiveness of TFA counseling in reducing anxiety among Hand Joint Stiffness pre-operative patients. The research findings indicated a p-value of < 0.05, suggesting that the TFA counseling method is effective in reducing anxiety levels in pre-operative patients with Hand Joint Stiffness. Patients who underwent TFA counseling demonstrated significant reductions in anxiety scores compared to the control group. Conclusion: These findings underscore the importance of a holistic approach in counseling pre-operative patients experiencing stiffness in the joint hand. The TFA counseling method can serve as an effective alternative in managing anxiety in patients before undergoing surgery.